Keluarga Kristiani di Tengah Arus Urban di Kota Malang - Raja, Fulbertus Bernadus (Aditya Wacana Pusat Pengkajian Agama Dan Kebudayaan, 2018)
Christian families have the task and demand to carry out, namely to make into practice or to realize Christian values within the families and the society at large. At the present time, modernity with all its impact has penetrated the very core of the society, particularly the families. This is practically a great challenge for Christian families, on the one hand to internalize Christian values and, on the other hand, to give some impact to the society. This research investigates the impact of modernity to Christian families in the city of Malang. The article then tries to encourage Christian families to be more open to this present trend and be wiser in coping it as a new field of their mission. The Christian families are expected to be able to actualize their faith in a new way within this new era.